Whole grain uncovered - Hazali, Norazlanshah (Tigas Pharma (M) Sdn. Bhd., 2012)
CEREAL GRAINY has long been a major part of our daily lives and we now consume rice on average three or two times a day. Other popular cereal grains-defined as as sourced from any plant within the grass family that yields an edible grain or seed - are wheat, barley, corn and oats.